KOSMARA: Konsep Pengembangan Ekonomi Pesantren dan Pengendalian Pola Perilaku Konsumtif Santri di Pondok Pesantren Nurul Jadid - Moh. Idil Ghufron, Kholid Ishomuddin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2021)
Pesantren Nurul Jadid is an Islamic boarding school founded by K.H. Zaini Mun'im which is located in Tanjung, Paiton, Probolinggo is one of the largest Islamic boarding schools in East Java. In a pesantren, students are taught how to be independent and learn to live qanaah, namely the attitude of being willing to accept or feel sufficient with what is obtained and to distance themselves from being dissatisfied and feeling excessive inadequacy. Consumptive lifestyles in the present era are often found in the midst of society. People's lifestyle in buying excess items occurs in adolescents, including students. Information about fashion, types of food and drink and so on can easily be obtained by them because of the easy access to the internet and other social media so that students who are expected to be able to control these patterns are eroded by technology that has begun to enter the pesantren. In addition, pesantren are also required to always develop the economy so that they can still exist and become an independent Islamic boarding schools so that the focus of the pesantren in educating students and prospective students is no longer constrained by economic problems. In Nurul Jadid Islamic boarding school, these efforts began by implementing the Kosmara program (Kos Makan Santri) which aims to control the consumptive patterns of students and make the pesantren independent in the economy. In this research, the method used is descriptive qualitative by conducting interviews with informants.